IPR Aimoré - Triticale cultivar of early maturity and wide adaptation. - Riede,Carlos Roberto (2016)
Abstract IPR Aimoré is a new triticale cultivar that combines earliness and high yield. In Value for Cultivation and Use trials carried out in 33 environments, involving the main triticale producing states, IPR Aimoré surpassed 4% the controls means, with mean yield of 4.955 kg ha-1.